DISCOUNT RATE: SELECTION METHODS IN UKRAINE - KARPUSHENKO, Maria; SHAPOVAL, Galyna; KARPUSHENKO, Oleg (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the main factors that influence the choice of the discount rate by Ukrainian enterprises, taking into account the external and internal risks of their activity. The discount rate is an important tool for evaluating the time value of money and making investment decisions. The correct choice of discount rate is critical for financial planning and investment analysis. In Ukraine, the choice of discount rate depends on a number of factors, including the macroeconomic situation, inflationary expectations, political stability and availability of financing. Ukrainian companies often face challenges related to market instability and high inflation, which affects the choice of discount rate. Choosing a discount rate is critical for making sound financial decisions in Ukraine. Basic methods, such as WACC, risk assessment method, analogue method, CAPM, can be applied taking into account the specific conditions of the Ukrainian market. It is important to take into account macroeconomic factors, political stability, availability of financing and peculiarities of tax legislation when determining the discount rate. WACC, the method of risk assessment, the method of analogues, CAPM were analyzed and it was determined that they can be applied in the activities of Ukrainian enterprises, taking into account the specific conditions of the Ukrainian market. The advantages and disadvantages of existing discounting methods are determined and the advantages and disadvantages of their application by Ukrainian enterprises are emphasized depending on the type of their activity. The expediency of applying a complex approach to determining the discount rate, taking into account the macroeconomic conditions of the enterprise’s functioning, political stability and tax legislation, as well as the availability and cost of financing in the domestic market, is substantiated. The application of a complex approach to the selection of the discount rate will allow to increase the accuracy of financial estimates and will contribute to the adoption of more informed investment decisions in the conditions of the Ukrainian market.